Synthesis of symmetrical biaryl compounds by homocoupling reaction. Issue 13 (29th March 2019) - Vasconcelos, Stanley N.S.; Reis, Joel S.; de Oliveira, Isadora M.; Balfour, Michael N.; Stefani, Hélio A.
Abstract: Since the development of the Ullmann coupling in the early 20th Century, there has been intense and continuous research on the syntheses of biaryl compounds, which appears as an interesting branch of organic chemistry. A myriad of methodologies for the synthesis of biaryl compounds have been studied and well established, including homocoupling methodologies, which in general are robust as well as consolidated strategies. Biaryl systems are quite relevant building blocks for the synthesis of more complex chemical structures. Besides the diversity of functional groups that can be used to promote a new aryl-aryl bond, there is a wide variety of transition metals that can act as catalyst in these processes. In this review, we summarized numerous methodologies of homocoupling reactions for the synthesis of symmetrical biaryl compounds. Graphical abstract: Image 1